Hambatan belajar siswa kelas VIII madrasah tsanawiyah pada materi fungsi - Qusnul Fianabila; Aiyub Aiyub (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
This research is motivated by the low level of students' understanding of the material on functions. This study aims to identify and analyze the learning obstacles faced by eight-grade MTs students in understanding the function material. The method used is qualitative research with a hermeneutic phenomological approach.. Data were collected through tests, questionnaires, and in-depth interviews. The results indicate three main categories of learning obstacle; ontogenic obstacles (psychological, isntrumental, and conceptual), didactic obstacles and epistemilogical obstacles. The findings also reveal that the primary problems students face are a lack of basic conceptual understanding, low learning motivation , and difficulties in applying knowledge to situations or problem types different from those usually taught by the teacher.. The novelty of this study lies in the use of a hermeneutic phenomological approach to deeply explore the experiences and meanings of learning ostacles from the students’ perspective, as well as categories: ontogenic, didactic, and epistemological. This research contributes to an in-depth analysis of students' learning experiences through a hermeneutic phenomenological approach, as well as recommendations for contextual learning strategies, the use of visual-interactive media, and individual guidance to address student learning barriers.